INTEGRATED SYSTEMS OF INFORMATION SECURITY IN COMPUTER NETWORKS - Loutsky, Georgy; Shyrotchin, Valerij; Mukhin, Vadim (International Journal of Computing, 2014)
In this paper we suggest the integrated security systems for computer networks, which are adaptive to certain network parameters. Also is suggested the approach to adaptive security systems parameters evaluation based on the analysis of information value changing in time. The main requirements to adaptive security systems are developed.